PENYULUHAN GUNA PENUNJANG KESUKSESAN USAHA UKM BERBASIS PEMBUKUAN USAHA LAPORAN LABA/RUGI - Emaya Kurniawati; Aprih Santoso; Sri Yuni Widowati (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The purpose of this activity is to provide counseling to support the success of SME-based business outreach of financial statements of profit / loss to the PKK Kelurahan Lor. Business group and to promote economic growth.The method used is the Business Evaluation Method and Counseling MethodAs a result, the PKK Kelurahan Panggung Lor Group has learned and gained knowledge about business accounting knowledge and is able to do business bookkeeping in the form of profit / loss reports.